On Some Problems of Strongly Ozaki Close-to-Convex Functions. (1st September 2020) - Maleki, Zahra; Shams, Saeid; Ebadian, Ali; Analouei Adegani, Ebrahim
Abstract : The purpose of the current paper is to investigate some geometric properties of the class F O ν, γ, called strongly Ozaki close-to-convex functions, such as strongly starlikeness and close-to-convexity. Further, we find sharp bounds on Fekete-Szegö functionals and logarithmic coefficients for functions belonging to the class F O ν, γ, which incorporates some known outcomes as the specific cases.